CEO board membership: implications for firm value. Issue 3 (26th July 2018) - Li, Michelle; Roberts, Helen
Abstract : Purpose: This paper aims to examine the relation between CEO board membership and firm performance. Design/methodology/approach: This paper investigates the relationship between firm performance and CEO board membership, applying two-stage least squares, propensity score matching and correcting for self-selection bias across a unique sample of publicly listed New Zealand firms that demonstrate a definitive variation in CEO board membership. Findings: This study finds that CEO board membership has a positive impact on firm performance, and these benefits are greater for more complex firms. Research limitations/implications: Firms with CEOs independent of the board are associated with lower firm performance. The results are consistent with CEO board members providing an important information transfer mechanism to the board, resulting in an increase in average firm performance. This benefit is greater for larger firms with more business segments. Originality/value: The paper tests for the impact of CEO board membership using a data set that demonstrates a definitive variation in CEO board membership.